Self‐Assembled Heterostructures: Selective Growth of Metallic Nanoparticles on V2–VI3 Nanoplates. Issue 38 (11th August 2017) - Dun, Chaochao; Hewitt, Corey A.; Li, Qi; Guo, Yang; Jiang, Qike; Xu, Junwei; Marcus, Gabriel; Schall, Drew C.; Carroll, David L.
Abstract : Precise control of the selective growth of heterostructures with specific composition and functionalities is an emerging and extremely challenging topic. Here, the first investigation of the difference in binding energy between a series of metal–semiconductor heterostructures based on layered V2 –VI3 nanostructures is investigated by means of density functional theory. All lateral configurations show lower formation energy compared with that of the vertical ones, implying the selective growth of metal nanoparticles. The simulation results are supported by the successful fabrication of self‐assembled Ag/Cu‐nanoparticle‐decorated p‐type Sb2 Te3 and n‐type Bi2 Te3 nanoplates at their lateral sites through a solution reaction. The detailed nucleation–growth kinetics are well studied with controllable reaction times and precursor concentrations. Accompanied by the preserved topological structure integrity and electron transfer on the semiconductor host, exceptional properties such as dramatically increased electrical conductivity are observed thanks to the pre‐energy‐filtering effect before carrier injection. A zigzag thermoelectric generator is built using Cu/Ag‐decorated Sb2 Te3 and Bi2 Te3 as p–n legs to utilize the temperature gradient in the vertical direction. Synthetic approaches using similar chalcogenide nanoplates as building blocks, as well as careful control of the dopant metallic nanoparticles or semiconductors, are believed to be broadly applicable to other heterostructures with novel applications. Abstract : First‐principles calculations are used to predict that the lateral edges of V2 –VI3 nanostructures are capable of initiating nucleation and in situ growth of a second phase. The simulation results are supported by the successful fabrication of self‐assembled Ag/Cu‐nanoparticle‐decorated p‐type Sb2 Te3 and n‐type Bi2 Te3 nanoplates at their lateral sites through a solution reaction.